FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPUASAN PENGGUNA APLIKASI SISTEM ABSENSI ONLINE DI STMIK STIKOM BALI - I Gusti Ngurah Satria Wijaya (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2017)
The level of user satisfaction online attendance system is one of the parameters that are widely used to assess the successful implementation of an online attendance system in an organization. Given the important role of online attendance system application, both in the implementation of online attendance by the user is a lecturer STMIK STIKOM Bali which took place quickly and easily and in terms of output produced is to obtain accurate results, required a measurement of the level of user satisfaction application attendance system online as a form of evaluation of the successful implementation of online attendance system that has been implemented so far. This study aims to examine the factors that affect the level of user satisfaction online attendance system application in STMIK STIKOM Bali. From the above problems it is necessary analysis to measure the level of user satisfaction in this case is the lecturer as a system user who can assess the satisfaction of the system. Measurement of user satisfaction in this problem by spreading the questionnaires that will be filled by lecturers STMIK STIKOM Bali by using multiple linier regression analysis method. The independent variables in this research are application quality, information quality, human resources, management support and operator service and the dependent variable is user satisfaction level of online attendance system. The results of this study can be concluded that based on the F test, application quality, information quality, human resources, management support and service operators simultaneously have a significant influence on the level of user satisfaction online attendance system application. Based on partial test, application quality, quality of information, human resources, management support and service of operator have positive effect to user satisfaction level of online attendance system application but not significant.